IMPLEMENTATION OF THE ADVENTURE OF ELEMENT GAME AS LEARNING MEDIA DURING COVID-19 PANDEMY - Amalia, Nurul; Lutfi, Achmad (Universitas Negeri Surabaya, 2024)
The aims of this research was to determine the effect of game The Adventure of Element as learning media on online learning during the corona pandemy. Target of this research is one Class XII as many as 27 students in Senior High School 2 Ngawi. This research used experimental methods, one-group-pretest-posttest. The students will be given pretest before using game learning media dan posttest after using game learning medium The students also will be given response questionnaire to find out the response of students about online learning using game. The result of this research showed that student learning outcomes after using game learning medium The Adventure of Elements experienced an increase with classical completeness reached 88,8%. The value obtained by the students on the pretest result of 40,74 and the postest result of 87,40 indicates tested n-Gain score of 0,8 in the high score. The response of Students about the game media obtained 86,49%. Based of these result, imply game learning medium The Adventure of Elements on learning during the corona outbreak on the chemical elements can improve students learning outcomes.